Man and animals - "Dmitriyev, Yuri" (Moscow, 1984)
Man's life on Earth is bound up fast with animals, birds and fish, insects and beasts, octopi and worms. But over the millennia man's relationships with animals have undergone, any changes. Animals supplied Man with food and clothes, inspired him with fear and gave him joy, originated customs and beliefs that some-times influenced the entire mode of life of the given societ, they have been enemies, friends and tutors.
Keywords: Psychology